Architectural design of core–shell nanotube systems based on aluminosilicate clay. Issue 13 (19th May 2022) - Stavitskaya, Anna; Rubtsova, Maria; Glotov, Aleksandr; Vinokurov, Vladimir; Vutolkina, Anna; Fakhrullin, Rawil; Lvov, Yuri
Abstract : An architectural approach for design of functional materials based on natural tubule nanoclay with functional elements placed selectively inside or outside these aluminosilicate tubes. Abstract : A nanoarchitectural approach to the design of functional nanomaterials based on natural aluminosilicate nanotubes and their catalysis, and practical applications are described in this paper. We focused on the buildup of hybrid core–shell systems with metallic or organic molecules encased in aluminosilicate walls, and nanotube templates for structured silica and zeolite preparation. The basis for such an architectural design is a unique Al2 O3 /SiO2 dual chemistry of 50 nm diameter halloysite tubes. Their structure and site dependent properties are well combined with biocompatibility, environmental safety, and abundant availability, which makes the described functional systems scalable for industrial applications. In these organic/ceramic hetero systems, we outline drug, dye and chemical inhibitor loading inside the clay nanotubes, accomplished with their silane or amphiphile molecule surface modifications. For metal–ceramic tubule composites, we detailed the encapsulation of 2–5 nm Au, Ru, Pt, and Ag particles, Ni and Co oxides, NiMo, and quantum dots of CdZn sulfides into the lumens or their attachment at the outside surface. These metal–clay core–shell nanosystems show high catalytic efficiency with increased mechanical and temperature stabilities. The combination of halloysite nanotubes with mesoporous MCM-41 silica allowed for a synergetic enhancement of catalysis properties. Finally, we outlined the clay nanotubes' self-assembly into organized arrays with orientation and ordering similar to nematic liquid crystals, and these systems are applicable for life-related applications, such as petroleum spill bioremediation, antimicrobial protection, wound healing, and human hair coloring.